Frequency of University Students’ Use of Addictive Substances and Attitudes Toward Addictive Substances - Çapuk, Hüseyin; Aylaz, Rukuye (Addicta: The Turkish Journal on Addictions, 2022)
This study aims to assess the level of knowledge, frequency of use, and attitudes toward addictive substances among university students. This descriptive study was conducted between December 2020 and May 2021. The sample of the research consists of 531 students who volunteered to participate in the research via “Google forms.” The statistical significance of the data was evaluated at the p .05 level. To analyze the data, percentage, mean, one-way analysis of variance, cross-tabulations, and Kruskal–Wallis test were used. In terms of students’ knowledge about addictive substances, it was found that 34.7% of students knew about marijuana, and 30.3% knew about heroin. It was found that 46.4% of students who tried to use substances for the first time were volatile, and 39.3% of them used marijuana. A statistically significant difference was found between the presence of students in an environment where addictive substances were used and their absence in terms of substance use tendency (p < .05). A more significant difference was found between the presence and absence of substance users in the family concerning substance use (p < .05). It was recommended to conduct awareness and education activities in family, friends, and universities in order to prevent substance use and addiction.
Keywords: Addictive substances; attitude; university students